1978
DOI: 10.7326/0003-4819-89-4-448
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Smoking Marihuana on Left Ventricular Performance and Plasma Norepinephrine

Abstract: In 14 healthy men we assessed the effects of smoking marihuana cigarettes containing 6 mg of delta-9-tetrahydrocannabinol on ultrasound measures of left ventricular function. Four of this group and four additional subjects also had measurements of plasma norepinephrine. Both heart rate and left ventricular performance (mean rate of internal diameter shortening [mean Vcf]) were significantly increased for at least 1 h after drug exposure compared with these values after placebo cigarettes. The immediate tachyca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0
2

Year Published

1988
1988
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 21 publications
0
48
0
2
Order By: Relevance
“…An increase in blood pressure, especially in the supine position, has been reported in some cases [18,19], whereas other studies reported orthostatic hypotension probably due to a reduction in autonomic reflex and in systemic vascular resistance [19,20]. An increase in sympathetic tone, reported by Gash et al [21], has been inferred from the rise in plasma norepinephrine levels [21].…”
Section: Discussionmentioning
confidence: 93%
“…An increase in blood pressure, especially in the supine position, has been reported in some cases [18,19], whereas other studies reported orthostatic hypotension probably due to a reduction in autonomic reflex and in systemic vascular resistance [19,20]. An increase in sympathetic tone, reported by Gash et al [21], has been inferred from the rise in plasma norepinephrine levels [21].…”
Section: Discussionmentioning
confidence: 93%
“…In support of this hypothesis, there is clear evidence of an arrhythmic effect of marijuana which has been linked to myocardial infarction in patients with normal coronary arteries as well as with sudden cardiac death [5, 6]. This is felt to be mediated by sympathetic nervous stimulation due to release of norepinephrine [7]. It would not be unreasonable to postulate a similar but more potent effect for synthetic cannabinoids, as they too have been found to precipitate myocardial infarction in teenagers in the absence of coronary artery disease [3].…”
Section: Discussionmentioning
confidence: 99%
“…Ylanen et al (1) report nonlethal ventricular arrhythmias in CPVT induced by tachycardia during exercise stress tests, but that syncope or sudden death is a consequence of more rapid or sustained VT or VF. Marijuana alone has been implicated with sinus tachycardia, sympathetic discharge, VT, and rarely sudden death, thus it is possible that his diagnosis was coincidental and that there was no direct correlation between the patient's drug ingestion and his CPVT (8)(9)(10). However, this patient never had arrhythmias with marijuana alone, thus synergy with the MDMA may have been required to reach a catecholamine release great enough to induce an arrhythmia (11,12).…”
Section: Discussionmentioning
confidence: 80%